Jeb Stuart correspondence - Stuart, Jeb, 1833-1864.
Photocopies of six letters and a fragment (1861 December 25-1862 April 8) written by Stuart to Laura Ratcliffe commenting on the Civil War and personal matters; and one letter (1862 Aug. 18) from Robert E. Lee to Stuart concerning cavalry tactics and other preparations for a campaign.
Negative photocopies produced from originals with the permission of Duddridge Nevitt.
United States and Confederate army officer. Full name: James Ewell Brown Stuart.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lee, Robert E. -- 1807-1870 -- Correspondence; Ratcliffe, Laura -- Correspondence; Confederate States of America. -- Army -- Cavalry; United States -- History -- Civil War, 1861-1865 -- Cavalry operations; United States -- History -- Civil War, 1861-1865 -- Campaigns; Army officers, Confederate